Peningkatan Efisiensi dan Produktivitas Produksi Melalui Inovasi pada UMKM Sopo Nyongko di Kabupaten Jember - Wiguna, Ardhitya Alam; Nizar Al Ardi , Aditya; Wahyu Pratama, Aditya; Mayasari, Financia; Akbar Ali, Reynaldi; Andriyanto, Dicky; Resya, Fachmi (J-Dinamika : Jurnal Pengabdian Masyarakat, 2026)
This Community Service (PkM) aims to improve the efficiency and productivity of UMKM Sopo Nyongko, an MSME located in Jember Regency. This MSME faces a major challenge: its manual and time-consuming production process, which limits production capacity and service speed. This limitation directly impacts the business's growth potential, especially in meeting increasing market demand. The solution offered in this PkM is the innovation and modernization of production tools, specifically through the implementation of improved, purpose-built equipment. The methods used involve several stages: 1) Needs analysis to understand the specific issues faced by UMKM Sopo Nyongko; 2) Designing and procuring innovative tools, such as semi-automatic equipment tailored to the business's scale; 3) Providing operational training to the UMKM's workers so they can operate the new equipment optimally; and 4) Mentoring and evaluation to ensure the sustainability and positive impact of the implemented innovations